Política exterior do Brasil para com o Uruguai no período de 1852 a 1864 - Cosso, Marcos Simões (2004)
The absence of internal political control, by the Uruguayan s governments, the clear intention to don t execute the Treaty made steady in 1851 with the Brazil and violations of the border to carry the Brazil to intervene in Uruguay again in 1864. Treat to the common understanding were tempted under the auspices of Irineu Evangelista de Souza, then baron of Mauá, and the counselor José Antonio Saraiva, minister plenipotentiary at Especial Mission in Prata. This last one, don t been attended in his pretensions, will emit an ultimatum, step reserved to an extreme situation. The failure of the Saraiva s mission moved the Empire to defence the interests of forty thousand Brazilians residing in that country, and to dismissal the president Atanasio Cruz Aguirre, blanco, at an following stage. To the attainment this second objective, joined their self the general Venâncio Flores, colorado, and the Brazilians Joaquim Marques Lisboa, then vice-admiral and baron of Tamandaré, and the marshal-of-field João Propício de Figueiredo Menna Barreto, future baron of São Gabriel. In spite of to conduct to Guerra da Tríplice Aliança, the Oriental campaign of 1864 contributed to the end of the caudilhismo in Uruguay and the establishment of the peace at the Brazilian-Orientals borders.